Development of Renewable Energy and Its Current Situation in Nepal - Neupane, Bibek Kanta; Parajuli, Chandra (NPRC Journal of Multidisciplinary Research, 2024)
This article provides an overview of the current state of electrification in Nepal, highlighting the significant progress made and the challenges that remain. It also outlines future projections and targets for the energy sector, emphasizing the role of renewable energy and energy efficiency in achieving sustainable development goals. In Nepal, the field of renewable energy is expanding quickly. While solar and wind energy are viewed as crucial supplements to help Nepal overcome its energy crisis, the country currently mostly relies on burning biomass for its energy requirements. Hydroelectricity is the most widely used type of renewable energy in Nepal. Nepal has a great opportunity to promote renewable energy sources. In addition to offering subsidies, the GoN has prioritized promoting RETs for last-mile electrification. Due to their lack of ready funds to invest, rural poor people are unable to benefit from technology and government subsidies. These technologies can be considered practical, dependable, and sustainable for modern development due to their established technologies, quality control systems, economics of the many renewable energy technologies (RETs), and rural social elements. The sustainability of any development in Nepal's last-mile regions depends on the diversification of the systems and the services they provide. The secondary data has been used and descriptive methodology adopted. Compared to traditional energy technologies, renewable energy technologies are clean energy sources with significantly reduced environmental impact. Instead of expensive energy imports, the majority of investments in renewable energy go toward building and maintaining the facilities.